Grounds of rebuting the judgment in criminal procedure: The methodology of writing the judgment as the biggest challenge - Živanović, Katarina S. (NBP. Nauka, bezbednosti, policija, 2023)
The legal and proper resolution of criminal matters represents the fundamental principle of modern criminal procedural legislation, since without its observance, the realization of the principle of a legal, democratic state, i.e. the realization of the fundamental principles of criminal procedural law, as well as the achievement of the goal of criminal proceedings and the protection of basic human rights, cannot be imagined. The prerequisite for the realization of the aforementioned principle is reflected in the correct application of adequate legal regulations, that is, in the correct and complete determination of the factual state by the court in criminal procedure. However, as the making of mistakes and omissions by the court in solving criminal matters, represents an immanent feature of the functioning of criminal justice, it is extremely important to establish which errors and omissions the courts make during the meritorious resolution of criminal proceedings. In this sense, with this research, the author established to what extent the courts make standardized errors and omissions, first of all from the aspect of the representation of all grounds of appeal and then also the representation of reason for appeal within the grounds of appeal of essential violations of the provisions of the criminal procedure. Special emphasis in the research was placed on errors and omissions made by courts when writing judgments, bearing in mind both the circumstance that the legislator prescribed it with a general clause, and the circumstance that the courts in most cases commit this essential procedural violation